Broadband Rayleigh wave attenuation by gradient metamaterials. (1st September 2021) - Wu, Xinyue; Wen, Zhihui; Jin, Yabin; Rabczuk, Timon; Zhuang, Xiaoying; Djafari-Rouhani, Bahram
Highlights: The combination of pillared and embedded core-shell units is found to emerge wider and lower bandgap frequency range comparing to their individual counterpart. The combined metamaterial attenuates wave transmission by −10 dB in a wider frequency range than the corresponding bandgap range which is explained by the symmetry of the Rayleigh wave and the eigenmodes in the dispersion. A gradient combined metamaterial is further designed and an extra wide wave attenuation frequency range, namely [4.3, 20.0] Hz, is achieved. Abstract: Broadband attenuation of low frequency acoustic waves in compact structure designs is a challenging issue, especially in the application to seismic waves. In this work, we propose a new seismic metamaterial constituted by a combination of two different attenuating structures, namely pillars above the ground and core-shell inclusions embedded in the soil. As compared to the two constituting parts, this structure enables us to broaden the bandgap while shifting it towards lower frequencies. Additionally, the analysis of the symmetry of the excited Rayleigh wave and the eigenmodes in the dispersion curves reveal that the frequency range of efficient wave attenuation in transmission is much wider than that of the corresponding bandgap. Finally, gradient combined metamaterial is designed to achieve wave attenuation in a broadband range of [4.3, 20.0] Ηz while the unit cell size keeps compact, of the order of 2 m. The results show practical and economic applications in ground surface vibration isolation to protect large infrastructures or civil engineering architectures. Graphical abstract: Image, graphical abstract